(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Simulation is a technique where the situation or a process is imitated. This process makes one to pretend the scenario. Aviation industry is one of the oldest industry which uses simulation technique to simulate the aviation technique. The main aim of having simulation lab is to make students acquire psychomotor skills before they actually treat the patients. Presently the National Medical Council of India has made it mandatory to have a skill lab but desirable to have a simulated mannequin for the training of medical students before actually treating the patients. Various advantages and disadvantages are appreciated in simulation technique. It is not very far that Dental council of India may make compulsory training of certain simulated modules in dentistry before treating the patient. Simulation lab in the pandemic like COVID has really helped people to undergo extensive training before treating patients, especially one who were catering the COVID ward or intensive care units. The simulation in dentistry is not a very old technique, certain technique are already in practice, but this article tries to highlight the necessity and gray areas where simulation can be improved for the benefit of students to learn and for the benefit of patients in view of safety.